Issues on halal meat in Malaysian and Indonesian markets - Ramli, M.A.; Salahudin, A.; Razak, M.I.A.; Idris, M.A.H.; Zulkepli, M.I.S. (2017)
In recent years, interest in meat issues and research has increased. Many consumers are concerned about the meat they eat because it's a main source of protein in a daily consumption. However in issues pertaining with meat, halal and safety are a vital focus for Muslim consumer, especially in Southeast Asia region. Some of the related issues in halal and safety meat are criminal and terrorist activities, including meat fraudulent such as adulterant substances (adulteration), substitution, livestock stolen, grey market product, smuggling, misrepresentation or mislabelling etc. In parallel with meat fraudulent activities, perpetrator tends to use a harmful and unsafety material in the meat product, namely glonggong meat, formalin meat, tiren meat, exotic meat etc. Thus, this review is intended to provide an overview of halal and safety issues in a meat product in the Malaysian and Indonesian markets. The findings show that there are various fraudulent actions that can threaten the lives of humans, animals and other food sources as well as opposed with Islamic Shariah guidance. Therefore, all parties need to mobilize a regional collaboration in combating food perpetrators and terrorist to ensure that the meat products in the market fit with halalan tayyiba criteria. In the same time, this collaboration will boost regional halal ecosystems grow rapidly, especially in Southeast Asia.